Political advertising and the portrayal of gender, colour and class in Jamaica's General Elections 2007 - Heron, Taitu (2008)
Examines how gender, colour and class were portrayed during the campaign of Jamaica's General Elections 2007, with particular emphasis on the candidates for the Office of Prime Minister: Mrs Portia Simpson- Miller and Mr. Bruce Golding.